(untitled) (Филологические заметки, 2019)
The previous scientific research generally accepted the oldest complete mythological tale from the ancient tradition for the Argive origin of the first Macedonian royal dynasty, for the first time recorded by Herodotus. According to him, three brothers, descendants of Temenus, thus known as Temenidae, came from Argos to Upper Macedonia, imposed their authority over other Macedonians and united them, founding their own royal dynasty known as Argeadae. This tradition was transformed according to the personal interest and prohelenic political commitments of Alexander I Philhellene, who wanted to resurrect his reputation in the Macedonian society, but also to provide support and prestige in the Hellenic world. The Macedonian royal dynasty was associated with the mythical hero Heracles, because of the prohelenic political reasons, so that the Macedonian kings would emphasize their cultural and divine origin and as seeming Hellenes be more directly involved in the Hellenic political struggles for dominance. Herodotus does not specify the location of the city of Argos, and in ancient times there were even seven cities and areas with the same naming. Due to unsustainable hypothesis of many researchers that the Macedonians were of Doric origin, it is usually identified with the Argos in the Peloponnese, which leads to the logical conclusion that Macedonian royal dynasty of the Argeadae has Hellenic origin. This is for centuries uncritically used or misused in historiography, particularly when the Hellenic origin of the ancient Macedonians is preferred. But all doubts for locating the city of Argos as the place of origin of the Macedonian royal dynasty of the Argeadae move away the historical sources that indicated that they were from Argos in Orestis, in Upper Macedonia. The myth of the foundation of the Macedonian kingdom is one of the earliest stories about the beliefs of the ancient Macedonians, with synthesized symbolism and wide area for various paper’s comments.